INFLUÊNCIA DA ADAPTAÇÃO DE PINOS DE FIBRA E DE TÉCNICAS RESTAURADORAS ALTERNATIVAS PARA PREENCHIMENTO DE CANAIS RADICULARES EXCESSIVAMENTE ALARGADOS - Gomes, Giovana Mongruel (2013)
The objectives of this study were 1) to evaluate the effect of the influence of the resin cement thickness (RCT) on bond strength (BS) and gap formation (GF) between glass fiber post (FP) and root dentin and 2) to evaluate the BS and fracture resistance (FR) of restorative techniques for filling oversized root canals. In experiment 1, the roots of 24 mandibular premolars (n=8 per group) were endodontically treated. After one week, the post spaces were prepared depending on the post adaptation inside the root canal, simulating an ideal adaptation (IdAd),medium adaptation (MeAd) and inadequate adaptation (InAd). All posts were cemented with Excite® DSC and Variolink® II. After a week of cementation, the RCT and GF were measured with the Image Tool software version 3.0, and the BS by the push-out test. In experiment 2, the roots of 84 mandibular premolars were endodontically treated and, after a week, the conduits were prepared in order to simulate an oversized root canal, except for the positive control group (PC), which was cemented one prefabricated fiber post (PFP) with the diameter compatible with the conduit. In the other oversized root canals, alternative restorative techniques for filling root canals were tested: NC - negative control (PFP with a smaller diameter than of the root canal), PA - PFP + accessory posts, DAP – direct anatomical post,IAP – indirect anatomical post and RR – root reinforcement with composite resin. All posts were cemented with the same adhesive system and resin cement. After indirect composite crowns cementation, the teeth were submitted to mechanical fatigue (1.2 X 106 cycles, 40 N) before the push-out BS test (n=8) and the FR test (n=6). The data of experiments 1 and 2 were analyzed by ANOVA and paired test (α=0.05). The experiment 1 showed that the smaller RCT resulted in better fiber post adhesion, that is, higher BS and lower GF. The experiment 2 showed that the use of direct and indirect anatomical posts resulted in the best performance both in BS and FR tests,and must be the first choice for FP cementation in flared roots with oversized root canals. Therefore, we concluded that the post adaptation to root canal affected significantly its retention. The better the post adaptation, the better the laboratory results. However, in the absence of this ideal condition, the use of direct and indirect anatomic posts should be the first choice for restoring flared root canals.